Bubble Trees -- The visualization of hierarchical information structures - Boardman, Richard (CHI'00: Extended abstracts of the SIGCHI conference on Human Factors in Computing Systems, 2000)
A tree visualization mechanism is proposed, based on the natural property of trees to recursively sub-categorize themselves into sub-trees. Each sub-tree is graphically represented as a bubble, which aggregates detail by enclosing lower-level information. Navigation and information retrieval are facilitated through an elegant set of browsing interactions. The interface is useful for tasks where users are required to develop a mental model of a classification system. The interactive nature of bubble trees allows users to explore and work out relationships for themselves.